Horror body as a bodily manifestation of visibility: 87 ore by Costanza Quatriglio. (1st November 2019) - Cesaro, Laura
AbstractTaking as a starting point the recent surge in film and television narratives constructed around and by surveillance technologies, as a metaphor of an omnipotent observation and dystopian motif in narrating a political and cultural change, this article aims to probe how surveillance movies suggest complex phenomenological dynamics in the relationships between body and device. While recent contributions on surveillance films (Kammerer 2004) focus on the practice of body control as a narrative mode, as an image and a show (Læ#169;fait 2013; Zimmer 2015), recent sociological contributions on surveillance recognize the destruction and annihilation of body placed under the aegis of the Great Eye (Haggerty 2011; Murakami Wood 2011). This article examines Costanza Quatriglio's film 87 ore: Gli ultimi giorni di Francesco Mastrogiovanni (2015) to describe the transition from bodies as narrative object to de-naturalizing the human body. The film narrates the night of 4 August 2009 when Mastrogiovanni, a 58-year-old primary school teacher, dies after 87 hours of agony following imprisonment. The film, in the canon of 'reality cinema', consists of 75 minutes of mechanical images recorded from above.